Association of vitamin D status with COVID‐19 disease severity in pediatric patients: A retrospective observational study. Issue 3 (6th April 2022) - Heidari, Solmaz; Mohammadi, Shooka; Fathi, Mohammadreza; Cigary, Shayan; Alisamir, Mohsen; Mirkarimi, Mohammadreza; Aminzadeh, Majid
Abstract: Background and Aims: Vitamin D deficiency is associated with increased vulnerability to respiratory infections. This study aimed to determine the potential relationships between coronavirus disease 2019 (COVID‐19) severity, serum vitamin D concentrations, and some inflammatory markers among pediatric COVID‐19 patients in Iran. Methods: A retrospective study was conducted among hospitalized pediatric COVID‐19 cases in Abuzar Hospital (Ahvaz, Iran) for 6 months. The COVID‐19 diagnosis was based on the real‐time reverse transcription‐polymerase chain reaction technique. Demographic and clinical data of patients were recorded. Patients with serum vitamin D levels lower than 20 ng/ml were assigned as Group 1 and those with serum vitamin D concentrations equal to or more than 20 ng/ml were considered as Group 2. Results: A total of 144 patients were enrolled. Their mean age was 80 ± 49 months (range: 1–16 years). Patients in Group 1 had significantly lower levels of serum vitamin D, calcium, and lymphocytes, as well as higher fibrinogen, d ‐dimer, and C‐reactive protein (CRP) levels compared with those in Group 2 ( p < 0.001). In addition, they had a significantly higher dry cough, fever, chest radiographic findings, respiratory rate, and longer hospital length of stay than patients in Group 2. Serum concentrations of vitamin D were positively correlated with levels of serum calcium, lymphocytes, and neutrophils but negatively correlated with CRP, fibrinogen, and d ‐dimer values. Furthermore, patients with moderate or severe courses of COVID‐19 had significantly higher inflammatory markers (CRP, d ‐dimer, and fibrinogen), as well as lower levels of serum calcium, vitamin D, lymphocytes, and neutrophils than those with mild COVID‐19 ( p < 0.001). In the multivariate analysis, fibrinogen level on admission was detected as the independent predictor of severe COVD‐19 (odds ratio = 1.06, 95% confidence interval: 1.03–1.09; p < 0.001). Conclusion: This study indicated associations between the severity of COVID‐19, serum vitamin D concentrations, and some inflammatory markers in pediatric COVID‐19 patients.